Biaxially oriented polypropylene-based film
By designing specific structures and compositions on the base layer and surface layer of the polypropylene film, the problems of insufficient adhesion and uneven surface energy caused by low surface energy of the polypropylene film are solved, excellent adhesion and sliding properties are achieved, and the processing performance of the film layer is improved.
Patent Information
- Application Number
- JP2024205791
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-07-03
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-06
AI Technical Summary
In the prior art, biaxially stretched polypropylene films lack adhesion due to small surface energy and low surface energy, and surface unevenness is prone to occur during the formation of the film layer, affecting the barrier properties and processing properties. At the same time, the use of antistatic agents leads to separation of the film layer from the solution, affecting the adhesion and uniformity of the film layer.
By designing specific structures on the base and surface layer of the polypropylene film, including the composition and processing technology of the base layer and surface layer, ensure that the wet tension, surface resistance, roughness and hardness of the surface layer are within a specific range, combined with an appropriate amount of antistatic agent, the surface characteristics are optimized to improve adhesion and slippage.
The polypropylene film maintains excellent adhesion and sliding properties during the film layer formation process, reduces the influence of barrier properties, avoids the problems of unevenness and adhesion of the film layer, and improves the processing performance.
Smart Images

Figure 2025019264000006 
Figure 2025019264000001 
Figure 2025019264000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a biaxially oriented polypropylene film. In processes such as deposition, coating, and lamination with other film materials, deposition films and coatings Excellent adhesion to films and adhesives, and suitable for processing with less wrinkling and blocking on rolls. This relates to oriented polypropylene films. [Background technology]
[0002] Conventionally, biaxially oriented polypropylene films have been very poor in terms of transparency and mechanical properties. Because of its excellent properties, it is used as a packaging material for various items including food and textile products. However, the problems with polypropylene films are as follows: For example, polypropylene resins are non-polar and therefore have low surface energy. For this purpose, deposition of inorganic or organic substances, coating, lamination with other materials and films, etc. It has been pointed out that the adhesion is insufficient.
[0003] In particular, when forming thin film layers by deposition or coating, not only adhesion but also protrusions due to surface irregularities are important. There is also the problem that a thin film cannot be formed at the raised portion, resulting in poor barrier properties. Propylene-based films have excellent flexibility and flatness, making them less slippery. Generally, anti-blocking agents are added to the surface to prevent blocking. This creates a rough surface, which makes it easier to form thin films by deposition or coating. This will result in insufficient barrier properties and other defects.
[0004] Furthermore, biaxially oriented polypropylene films are used for various food packaging applications. In order to prevent powders and dry goods from sticking to the surface due to static electricity, an antistatic agent is included in the film. It is common to increase the antistatic properties by bleeding onto the surface. If the inhibitor is on the surface of the film, the coating will repel the solution, causing failure.
[0005] Various methods have been proposed to address these problems. Mix branched polypropylene into the resin and transform the polypropylene's β crystals into α crystals. This creates unevenness on the film surface, effectively eliminating the need for inorganic or organic anti-blocking agents. A method for improving slipperiness without using a binder has been disclosed (see, for example, Patent Document 1). However, since only homopolypropylene with high stereoregularity is used, the surface It is hard and adheres well to thin films and coating layers after processing such as deposition, coating, and lamination. Gender is not taken into consideration.
[0006] On the other hand, antistatic agents are eliminated as much as possible, and the film surface is made uneven, so that ink and other materials can be easily removed. A method for improving adhesion when laminating with a film (for example, see Patent Document 2) is disclosed. It is being done. However, there is a need to examine the barrier properties and processability of thin films formed by deposition or coating. Higher demands are being made. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2007 / 094072 [Patent Document 2] International Publication No. 2018 / 142983 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a method for producing a biaxially oriented polypropylene film having excellent transparency and mechanical properties. Adhesive for deposition films, coating films, and lamination with other films without compromising properties It has excellent adhesion to the film, and has excellent film slippage and winding quality during processing. The present invention aims to provide a propylene film. [Means for solving the problem]
[0009] The present invention, which has solved the above problems, provides a substrate layer (A) mainly composed of a polypropylene-based resin and A surface layer (B) is attached to one surface of the base layer (A), and a surface layer (B) is attached to the opposite surface of the base layer (A). The surface layer (B) satisfies the following (1) to (5), and the surface layer (C ) is a biaxially oriented polypropylene film that satisfies the following (6) and (7). (1) The wetting tension is 38 mN or more. (2) The surface resistance is 14.0 Log Ω or more. (3) The arithmetic mean roughness (Ra) is 3.0 or more and 5.5 nm or less. (4) Martens hardness is 248N / mm 2 The following is the result. (5) The center surface average roughness (SRa) is 0.010 or more and 0.026 μm or less. (6) The center surface average roughness (SRa) is 0.020 μm or more. (7) Martens hardness: 270N / mm 2 That's all.
[0010] In this case, the dynamic friction coefficient of the biaxially oriented polypropylene film is 0.6 or less. It is preferable that there is.
[0011] In this case, the haze value of the biaxially oriented polypropylene film is 5% or less. It is preferable that:
[0012] Furthermore, in this case, the maximum peak height Rp+maximum valley depth Rv of the surface layer (B) It is preferable that the thickness is 30 to 50 nm.
[0013] Furthermore, in this case, the air release time of the biaxially oriented polypropylene film It is preferable that the time is 10 seconds or less.
[0014] Furthermore, in this case, the thickness of the biaxially oriented polypropylene film is 9 μm. It is preferable that the thickness is not less than 200 μm.
[0015] Furthermore, in this case, the biaxially oriented polypropylene film and the non-oriented polypropylene film are Laminates with ethylene films are preferred.
[0016] Furthermore, in this case, the laminate strength of the laminate is 2.0 g / 15 mm or more. It is preferable that the temperature is above 100° C. Effect of the Invention
[0017] The biaxially oriented polypropylene film of the present invention has excellent transparency and mechanical properties. Without compromising the properties, it can be used as a thin film or coated film after deposition, coating, or lamination with other films. It exhibits excellent adhesion to the coating layer and other films, and also has good slip properties and blocking resistance. It was suitable for processing raw material rolls. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is an explanatory diagram of the installation of an apparatus and a sample film used to measure the air release time (seconds). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The biaxially oriented polypropylene film of the present invention is a film having a polypropylene resin as a main component. A substrate layer (A), a surface layer (B) on one side of the substrate layer (A), and a surface layer (B) on the substrate layer (A). The surface layer (C) is disposed on the opposite side to the surface layer (B), and the surface layer (B) satisfies the following (1) to (5): The surface layer (C) satisfies the following (6) and (7). (1) The wetting tension is 38 mN or more. (2) The surface resistance is 14.0 Log Ω or more. (3) The arithmetic mean roughness (Ra) is 3.0 or more and 5.5 nm or less. (4) Martens hardness is 248N / mm 2 The following is the result. (5) The center surface average roughness (SRa) is 0.010 or more and 0.026 μm or less. (6) The center surface average roughness (SRa) is 0.020 μm or more. (7) Martens hardness: 270N / mm 2 More than this is preferable. Here, the wetting tension of the surface layer (B) is the mixture reagent determined to wet the film surface. A numerical value indicating surface tension (mN / m) and related to the wettability of printing inks and adhesives. It is. The surface resistance of the surface layer (B) varies depending on the amount of antistatic agent present on the surface. The smaller the amount of antistatic agent present on the surface, the higher the surface resistance.
[0020] The arithmetic mean roughness (Ra) of the surface of the surface layer (B) is measured using a scanning probe microscope (AFM). The measurement length in both the X and Y directions was measured in the dynamic mode within a range of 2 μm. After correcting the image (tilt, line fit, noise line removal), (1994) was used as the definition of the arithmetic mean roughness. The arithmetic mean roughness (Ra) of a 2 μm square area measured by AFM was determined by anti-blocking agents and lubricants. It is an index that shows the unevenness of the resin itself, excluding the relatively large hills and valleys formed by processing. It is related to the adhesion with resin in deposition, coating, lamination, etc. This indicates that the surface is uneven and the surface area of the resin that adheres to it during processing is large, and this leads to poor adhesion. This is different from the maximum peak height Rp+maximum valley depth Rv, which will be described later.
[0021] The Martens hardness of the surface layer (B) and the surface layer (C) was measured using a dynamic ultra-microhardness tester. The hardness of the resin was measured when a needle tip with a curvature radius of 0.1 μm or less was pressed into the surface by about 0.1 μm. The small Martens hardness of the surface layer (B) indicates that the surface is soft. This shows that the resin surface has high conformability during processing, and the adhesion is improved. A high surface hardness indicates a hard surface, which is shaped by antiblocking agents and lubricants. The resulting convex parts sink less, improving sliding properties and blocking resistance while keeping the contact area small. To rise.
[0022] The center surface average roughness (SRa) of the surface layer (B) and surface layer (C) is measured using a three-dimensional roughness gauge. The measurement length in the X direction was 1 mm, and the feed pitch in the Y direction was 2 μm. The number of recording lines was 99, the height direction magnification was 20,000 times, and the cutoff was 80 μm. It was determined in accordance with the definition of arithmetic mean roughness described in S-B0601 (1994).
[0023] The average roughness of the central surface (SRa) is relatively large due to the anti-blocking agent and lubricant. It is an index of surface irregularities, including large peaks and valleys, and is used to measure the film's slipperiness and roll stiffness. This is related to blocking between films. A large SRa means that the surface is uneven. The contact area on the surface is small, which prevents blocking between films and sliding with metals. The thickness becomes smaller, and the slipperiness and blocking resistance are improved.
[0024] (1) Base material layer (A) The polypropylene constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention The resin is a polypropylene homopolymer that does not contain a copolymer component, and ethylene and / or Polypropylene resin copolymerized with 0.5 mol% or less of α-olefin having 4 or more carbon atoms The copolymerization component is preferably 0.3 mol % or less, more preferably 0.1 mol % or less. A polypropylene homopolymer containing no copolymer component is more preferred, and a polypropylene homopolymer containing no copolymer component is most preferred. The amount of copolymerization of ethylene and / or α-olefin having 4 or more carbon atoms is 0.5 mol % or less If the temperature is lower than this, the crystallinity and rigidity are less likely to decrease, and the thermal shrinkage rate at high temperatures is less likely to increase. These resins may be blended and used.
[0025] The polypropylene constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention It is an index of stereoregularity of the resin. 13 Mesopentad fraction ([m The percentage of the chromaticity of the chromate is preferably 98% or more and 99.5% or less. More preferably, The polypropylene resin is preferably 98.1% or more, and more preferably 98.2% or more. If the mesopentad ratio is small, the elastic modulus will be low and the heat resistance may be insufficient. 99.5% is a realistic upper limit.
[0026] The polypropylene constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention The mass average molecular weight (Mw) of the resin is preferably 180,000 or more and 500,000 or less. stomach. If it is less than 180,000, the melt viscosity is low, so it is not stable when cast, and film forming properties are poor. If Mw exceeds 500,000, the amount of components with molecular weights of 100,000 or less may deteriorate. 35% by mass, which reduces the thermal shrinkage rate at high temperatures. A more preferable lower limit of Mw is 190,000, and even more preferably 200,000. A more preferred upper limit of Mw is 320,000, even more preferably 300,000, and particularly preferably The most common is 250,000.
[0027] The polypropylene constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention The number average molecular weight (Mn) of the resin is preferably 20,000 or more and 200,000 or less. If it is less than 20,000, the melt viscosity is low, so it is not stable when cast and film forming properties are poor. If it exceeds 200,000, the heat shrinkage rate at high temperatures decreases. A more preferable lower limit of Mn is 30,000, even more preferably 40,000, and particularly preferably The upper limit of Mn is preferably 50,000, more preferably 80,000, and even more preferably 7 0,000, and particularly preferably 60,000.
[0028] In addition, Mw / Mn, which is an index of molecular weight distribution, is In the case of resins based on cellulose acetate, the range is preferably 2.8 or more and 10 or less. More preferably, the range is 2.8 or more and 8 or less. Preferably, the ratio is 2.8 or more and 6 or less, and particularly preferably, the ratio is 2.8 or more and 5.4 or less. The lower limit is preferably 3 or more, and more preferably 3.3 or more. The molecular weight distribution of polypropylene resins is determined by multi-stage processing of components with different molecular weights. Polymerization can be done in a run-on process, components of different molecular weights can be blended offline in a kneader, or different Polymerization can be carried out by blending catalysts with the desired performance, or by using a catalyst that can achieve the desired molecular weight distribution. It is possible to adjust the amount of heat generated by the heater.
[0029] The polypropylene constituting the base layer (A) of the biaxially oriented polypropylene film of the present invention When the Mw / Mn ratio of the resin is in the range of 2.8 or more and 5.4 or less, the melt flow rate ( MFR (230℃, 2.16kgf) is 2g / 10min or more and 20g / 10min or less. is preferred. The lower limit of the MFR of the polypropylene resin of the base layer (A) is preferably 3 g / 10 min. More preferably, the ratio is 4 g / 10 min, and even more preferably, 5 g / 10 min. The upper limit of the MFR of the polypropylene resin of the base layer (A) is preferably 15 g / 10 min. It is more preferable that the viscosity is 10 g / 10 min, and further more preferable that the viscosity is 12 g / 10 min. The Mw / Mn and MFR of the polypropylene resin constituting the base layer (A) are within this range. If the film has a high heat shrinkage rate, the film can be kept small even at high temperatures. Also, the film has good adhesion to the cooling roll. It has good film-forming properties.
[0030] (2) Surface layer (B) The arithmetic mean roughness (R a) is preferably 3.0 to 5.5 nm. If it is less than 0.0 nm, the surface area of the surface layer (B) is small, and it is difficult to perform deposition, coating, lamination, etc. When processing with a metal plate, the adhesion strength decreases. The arithmetic mean roughness (Ra) is 5. If it exceeds 5 nm, the surface irregularities are large, and holes occur during deposition or coating, resulting in poor barrier properties. etc. become defective. The arithmetic mean roughness (Ra) of the surface of the surface layer (B) is preferably 3.2 nm or more, and more preferably 3.3 nm or more is more preferable, 3.5 nm or more is particularly preferable, and 4.0 nm or more is most preferable. It is nice. In order to make the arithmetic mean roughness (Ra) of the surface of the surface layer (B) 3.0 to 5.5 nm The polypropylene resin composition forming the surface layer (B) has a melt flow rate It is preferable to use a mixture of two or more polypropylene resins with different MFR. In this case, the difference in MFR is preferably 3 g / 10 min or more, and more preferably 3.5 g / 10 min or more. More preferably, it is equal to or greater than this. As described above, the polypropylene resin mixture may include two or more polypropylene resins. When the difference in melt flow rate (MFR) is different, the crystallization of each polypropylene resin It is assumed that the difference in the crystallization rate and degree of crystallization makes it easier for unevenness to form on the surface. The degree of crystallinity of polypropylene resin is high, and the cooling of unstretched sheets during film production If the stretching speed is too slow, the surface irregularities caused by spherulites will become large. Sometimes, if the stretching temperature is too high and the surface unevenness becomes large, the arithmetic average roughness (Ra) will be less than 5.5 nm. Caution is required as this may be exceeded. Polypropylene resins with smaller MFR are ethylene and / or polypropylene resins with 4 carbon atoms. Polypropylene copolymerized with the above α-olefins can also be used. The α-olefins are 1-butene, 1-hexene, 4-methyl-1-pentene, 1 -octene, etc. In addition, maleic acid, which has polarity as another copolymer component, etc. may also be used. Ethylene and / or α-olefins having 4 or more carbon atoms, other copolymer components in total The copolymerization amount is preferably 8.0 mol % or less. If the copolymerization amount exceeds 8.0 mol %, the film In some cases, the coating may turn white, resulting in a poor appearance, or the coating may become sticky, making it difficult to form a film. These resins may be used in combination of two or more. The resin may be copolymerized in an amount of more than 8.0 mol %, but the blend is a monomer-based copolymer. The amount of monomers other than propylene in the copolymer is preferably 8.0 mol % or less. In addition, the polypropylene resin with a larger MFR is the copolymer polypropylene mentioned above. Alternatively, a homopolypropylene resin can be used. Polypropylene resin with a smaller MFR and polypropylene resin with a larger MFR The mixing ratio of these is preferably in the range of 1% by weight / 99% by weight to 49% by weight / 51% by weight. % / 99% by weight to 30% by weight / 70% by weight is more preferable, and 1% by weight / 99% by weight is more preferable. A range of up to 10% by weight / 90% by weight is even more preferable.
[0031] In addition, the polypropylene constituting the surface layer (B) of the biaxially oriented polypropylene film of the present invention The pyrene-based resin composition has an MFR of 1.0 g / 10 min or more and 10.0 g / 10 min or less. The lower limit of the MFR of the polypropylene resin composition of the surface layer (B) is preferably 2.0. g / 10 min is more preferable, and 3.0 g / 10 min is even more preferable. The polypropylene-based resin constituting the surface layer (B) is particularly preferably 4.0 g / 10 min. The upper limit of the MFR of the resin composition is more preferably 9.0 g / 10 min, and more preferably 8.0 g / It is more preferable that the viscosity is 10 minutes, and particularly preferable that the viscosity is 5.5 g / 10 minutes. Within this range, the film-forming property is good and the appearance is also excellent. If the MFR of the polypropylene-based resin composition is less than 1.0 g / 10 min, the polypropylene constituting the base layer (A) may be easily deteriorated. When the MFR of the propylene-based resin composition is high, the difference in viscosity between the substrate layer (A) and the surface layer (B) becomes large. Since the thickness of the film becomes large, unevenness (unevenness of the original film) is likely to occur during film formation. When the MFR of the polypropylene resin composition exceeds 10 g / 10 min, the adhesion to the cooling roll increases. The adhesion becomes poor, air gets trapped, the smoothness becomes poor, and the defects become more numerous. There it is.
[0032] In addition, the surface of the surface layer (B) of the biaxially oriented polypropylene film was measured using a three-dimensional roughness meter. The center surface average roughness (SRa) is preferably 0.010 μm or more and 0.026 μm or less. The center surface average roughness (SRa) of the surface layer (B) is 0.012 μm or more, and 0.02 More preferably, the thickness is 5 μm or less, and even more preferably, the thickness is 0.015 μm or more and 0.025 μm or less. The thickness of the surface layer (B) is preferably 0.020 μm or more and more preferably 0.024 μm or less. If the average roughness (SRa) of the core surface is less than 0.010 μm, the surface irregularities are small and the film cannot slide. The surface of the surface layer (B) If the center surface average roughness (SRa) exceeds 0.026 μm, aluminum deposition or coating is required. When applying a thin film layer, the anti-blocking agent may penetrate the thin film layer, or the thin film may form on the side of the convex part. The surface of the surface layer (B) may not be formed, resulting in a decrease in barrier properties and poor adhesion. There are several methods to keep the average roughness (SRa) within the specified range, but anti-blocking agents It is possible to adjust the average particle size and the amount of addition. Anti-blocking agents include silica, calcium carbonate, kaolin, zeolite, etc. Among inorganic particles and organic particles such as acrylic, polymethacrylic, and polystyrene particles Among these, silica and polymethacrylic acid are preferred. It is particularly preferred to use particles. The preferred average particle size of the antiblocking agent is 1.0 μm. m or more and 3.0 μm or less, more preferably 1.0 μm or more and 2.7 μm or less. The average particle size is measured by taking a photograph using a scanning electron microscope and then analyzing it with an image analyzer. The horizontal Feret's diameter was measured using an instrument, and the average value was expressed. The amount of anti-blocking agent added affects haze, dynamic friction coefficient, center surface average roughness (SRa), The amount of additive added to the surface layer (B) and surface layer (C) is adjusted so that the air release time falls within the specified range. If so, there are no particular restrictions.
[0033] The surface resistance of the surface layer (B) of the biaxially oriented polypropylene film of the present invention is 14 It is preferable that the surface resistance is Log Ω or more. If the surface resistance is 14 Log Ω or more, the deposited film and Improves adhesion to coating films and adhesives. Surface resistance is 14.5 Log Ω or more. More preferably, the surface resistance is 14 Log Ω or more, and even more preferably, the surface resistance is 15 Log Ω or more. If it is less than LogΩ, not only will the adhesion strength decrease, but the antistatic agent that bleeds to the surface layer (B) will also The adhesive will repel the coating, resulting in a defective coating. To achieve a surface resistance of 14 Log Ω or more, The additives such as antistatic agents and antifogging agents are not used as much as possible. ) may bleed onto the surface of the surface layer (B), so care must be taken. It is essential.
[0034] The surface wetting tension of the surface layer (B) of the biaxially oriented polypropylene film of the present invention is 38m If the wetting tension is 38 mN / m or more, the deposited film or the coating film can be easily formed. This improves adhesion to the adhesive used for laminating the coating film and other film components. To achieve a tension of 38 mN / m or more, additives such as antistatic agents and surfactants are used. However, these methods have the effect of lowering the surface resistance, It is preferable to carry out a physicochemical surface treatment such as a Rona treatment or a flame treatment. For example, in corona treatment, it is preferable to use a preheat roll and a treatment roll and perform discharge in the air. I wish.
[0035] The Martens hardness of the surface layer (B) of the biaxially oriented polypropylene film of the present invention is 248 N / mm 2 It is preferable that the resistance is less than or equal to 245 N / mm 2 The following is true: More preferably 240N / mm 2 or less, and particularly preferably 235 N / mm 2 Below and most preferably 230N / mm 2 The following is the result. Martens hardness is 248N / mm 2 If it exceeds this limit, the surface is hard and the resin surface is The Martens hardness is 248N / mm 2 Make it less than To achieve this, ethylene and / or α-olefins with 4 or more carbon atoms and other copolymer components are used. This is possible by adding . Also, the film stretch ratio is lowered, and the molecular chain orientation is reduced. It is also possible to reduce the Martens hardness by The surface layer (B) of the biaxially oriented polypropylene film of the present invention has a Martens hardness of 200 N / mm 2 It is preferable that the resistance is equal to or higher than 210 N / mm 2 That's all.
[0036] The maximum surface area of the surface layer (B) of the biaxially oriented polypropylene film of the present invention was measured by AFM. It is preferable that the peak height Rp+maximum valley depth Rv is 30 to 50 nm. B) The lower limit of the maximum peak height Rp + maximum valley depth Rv of the surface is preferably 32 nm, and more preferably 35 nm. m is more preferably 38 nm, and particularly preferably 38 nm. The upper limit of the maximum valley depth Rv is more preferably 48 nm, and particularly preferably 45 nm. The maximum valley depth Rv and the maximum blockage depth Rp are not due to the anti-blocking agent, but due to the unevenness of the resin itself. If the maximum peak height Rp + maximum valley depth Rv is 30 nm or more, the roll state The surface layer (C) is in contact with the air escaping and the blocking resistance is improved. The surface area of (B) is increased, improving adhesion to the deposition layer or coating layer. However, air release and blocking resistance are measured using the central surface roughness (SRa ), so even if the maximum peak height Rp and maximum valley depth Rv are less than 30 nm, (B) If the central surface roughness (SRa) of the surface layer (C) is large, air leakage and blocking resistance are improved. If the maximum peak height Rp + maximum valley depth Rv is 50 nm or less, In this case, the surface irregularities are not too large, and the deposition layer or coating layer is less likely to come off, and burrs are reduced. The quality and other aspects of the product will improve.
[0037] (3) Surface layer (C) The surface of the surface layer (C) of the biaxially oriented polypropylene film of the present invention was measured using a three-dimensional roughness meter. The center surface average roughness (SRa) is preferably 0.020 μm or more. The center surface average roughness (SRa) of the surface is preferably 0.022 μm or more, and more preferably 0.025 μm or more. is more preferable, and 0.028 μm is particularly preferable. If the center surface average roughness (SRa) of the surface layer (C) is less than 0.020 μm, the surface irregularities The film has poor slipperiness, poor air release time between films, and poor blocking resistance. There are several methods to keep the center surface average roughness (SRa) of the surface layer (C) within the specified range. However, it is possible to adjust the average particle size and amount of the antiblocking agent. The surface of the surface layer (C) of the biaxially oriented polypropylene film of the present invention was measured using a three-dimensional roughness meter. It is preferable that the center surface average roughness (SRa) is 0.040 μm or less.
[0038] In addition, the Martens hardness of the surface layer (C) of the biaxially oriented polypropylene film is 270N. / mm 2 More preferably, it is 275N / mm 2 More than that, even more preferred Or 280N / mm 2 More preferably, 285N / mm 2 That's all. Martens hardness is 270N / mm 2 If it is less than this, the surface is soft and the anti-blow coating added The blocking agent sinks into the resin, causing the lubrication and blocking resistance to deteriorate. 270N / mm 2 or more, ethylene and / or α- It is also preferable to use polypropylene copolymerized with 0.5 mol % or less of olefin, 0.1 mol% or less is more preferable, and completely homopolypropylene containing no copolymer component is most preferable. It is also preferable that the mesopentad fraction ([mmmm]%) of the constituent polypropylene is 9. It is also possible to increase the Martens hardness by increasing the crystallinity by making the content 8% or more. The Martens hardness of the surface layer (C) of the biaxially oriented polypropylene film is 350N / mm 2 It is preferable that:
[0039] The polypropylene resin used in the present invention is a polypropylene resin produced using a Ziegler-Natta catalyst, a metallocene catalyst, or the like. It is obtained by polymerizing the raw material propylene using a known catalyst. To eliminate the bonds, a Ziegler-Natta catalyst is used, which allows for highly stereoregular polymerization. It is preferable to use a solvent. The method for polymerizing the raw material propylene may be a known method. For example, Polymerization in an inert solvent such as xane, heptane, toluene, or xylene. a method of polymerizing in a gas phase by adding a catalyst to a gaseous monomer, or and a method of polymerizing these in combination.
[0040] The base layer (A) and / or the surface layer (B) of the biaxially oriented polypropylene film of the present invention The surface layer (B) and / or the surface layer (C) may contain additives or other resins. Examples of additives include antioxidants, ultraviolet absorbers, nucleating agents, adhesives, anti-fogging agents, and flame retardants. Examples of other resins include the resins used in the present invention. Polypropylene resins other than those made of propylene and ethylene and / or Random copolymers, which are copolymers with α-olefins having 4 or more carbon atoms, and various elastomers These are polymerized sequentially using multi-stage reactors, or polypropylene Resin is blended in a Henschel mixer, or a master made in advance using a melt kneader is used. - Dilute the pellets with polypropylene to the desired concentration, or melt and knead the entire amount in advance. It may be used as such.
[0041] (3) Biaxially oriented polypropylene film The biaxially oriented polypropylene film of the present invention has a structure of surface layer (B) / base layer (A) / surface layer (C) Three-layer structure: surface layer (B) / intermediate layer (D) / base layer (A) / intermediate layer (D) / surface layer ( C), four-layer structure of surface layer (B) / base layer (A) / middle layer (D) / surface layer (C), or more The laminate may have a multi-layer structure.
[0042] The total thickness of the biaxially oriented polypropylene film of the present invention is 9 μm or more and 200 μm or less. is preferable, 10 μm or more and 150 μm or less is more preferable, 12 μm or more and 100 μm or less is more preferable. It is more preferable that the thickness is 15 μm or more and particularly preferable that the thickness is 15 μm or more and 80 μm or less.
[0043] The thickness of the surface layer (B) and the base layer (A) in the biaxially oriented polypropylene film of the present invention The ratio of the thickness of the total surface layer (B) to the thickness of the total base layer (A) is 0.01 or less. It is preferable that the ratio is 0.02 or more and 0.40 or less. It is preferably 0.03 or more and 0.30 or less, and more preferably 0.04 or more and 0 It is particularly preferable that the thickness of the total surface layer (B) / the thickness of the total base layer (A) is 0.20 or less. If it exceeds 0.50, the shrinkage rate tends to increase.
[0044] In addition, the thickness of the surface layer (C) and the base layer (A) in the biaxially oriented polypropylene film The ratio of thickness of the total surface layer (C) to the total base layer (A) is 0.01 or more. It is preferably 0.50 or less, and more preferably 0.02 or more and 0.40 or less. It is preferable that the ratio is 0.03 or more and 0.30 or less, and more preferable that the ratio is 0.04 or more and 0.2 It is particularly preferable that the thickness of the total surface layer (C) / the thickness of the total base layer (A) is 0. If it exceeds 50, the haze increases and transparency decreases depending on the amount of antiblocking agent added. It gets worse.
[0045] In addition, the thickness of the base layer (A) relative to the thickness of the entire film, or the thickness of the base layer (A) and The total thickness of the intermediate layer (D) is preferably 50% or more and 99% or less, and more preferably Preferably, the range is 60% or more and 97% or less, more preferably 70% or more and 90% or less, and most preferably Above 80% and below 92%.
[0046] The haze of the biaxially oriented polypropylene film of the present invention is preferably 5% or less, and more preferably 0.2 % or more and 5.0% or less is more preferable, 0.3% or more and 4.5% or less is even more preferable, and 0.4 % or more, and 4.0% is particularly preferable. When the content is in the above range, it is easy to use in applications where transparency is required. Haze can occur, for example, when the stretching temperature, heat setting temperature, or cooling roll temperature is too high. When the cooling rate of the unstretched (raw) sheet is slow or there is too much low molecular weight component, the sheet becomes poor. By adjusting these factors, it is possible to keep the haze within the above range. The method of determination will be described later.
[0047] The biaxially oriented polypropylene film of the present invention has a tensile modulus in the machine direction of 1.8 or more, Preferably 0.0GPa or less, but 2.0GPa or more and 3.7GPa or less More preferably, the pressure is 2.1 GPa or more and 3.5 GPa or less. A pressure of 0.2 or more and 3.4 GPa or less is particularly preferred. The tensile modulus in the transverse direction of the biaxially oriented polypropylene film of the present invention is 3.8 GPa or more. Preferably, the pressure is 8.0 GPa or more, and more preferably, 4.0 GPa or more and 7.5 GPa or less. It is more preferable that the pressure is 4.1 GPa or more and further preferably 7.0 GPa or less. It is particularly preferable that the tensile modulus is 4.2 GPa or more and 6.5 GPa or less. Within this range, the film will be strong and can be used even if it is thin, so the use of film is possible. This allows the dosage to be reduced. The method for measuring the tensile modulus will be described later.
[0048] In the biaxially oriented polypropylene film of the present invention, the thermal shrinkage in the longitudinal direction at 150°C The ratio is preferably 0.2 to 15.0%, and more preferably 0.3 to 13.0%. More preferably, the content is 0.5% or more and 11.0% or less, and even more preferably, 0.5% or more and 11.0% or less. It is particularly preferable that the heat shrinkage rate is in the above range. This is an excellent film and can be used in applications where it may be exposed to high temperatures. In addition, if the heat shrinkage rate at 150°C is up to about 1.5%, for example, by increasing the amount of low molecular weight components, stretching It is possible to lower the temperature by adjusting the conditions and heat fixing conditions, but to lower the temperature, it is necessary to perform an offline It is preferable to carry out an annealing treatment or the like. In the biaxially oriented polypropylene film of the present invention, the thermal shrinkage in the transverse direction at 150°C The ratio is preferably 0.5 to 30.0%, and more preferably 0.5 to 25.0%. More preferably, the content is 0.5% or more and 20.0% or less, and even more preferably, 0.5% or more and 20.0% or less. It is particularly preferable that the heat shrinkage rate is in the above range. It can be said to be a film with excellent properties and can be used in applications where it may be exposed to high temperatures. In addition, if the heat shrinkage rate at 150°C is up to about 1.5%, for example, by increasing the amount of low molecular weight components, stretching It is possible to adjust the stretching and heat setting conditions, but to lower it below that, offline It is preferable to perform annealing treatment at 40° C. The method for measuring the thermal shrinkage will be described later.
[0049] The dynamic friction coefficient of the biaxially oriented polypropylene film of the present invention is 0.6 or less. It is preferable that the friction coefficient is 0.55 or less, more preferable that the friction coefficient is 0.50 or less. If the friction coefficient is 0.6 or less, the film can be unwound smoothly from the roll film. It is easy to print on. The coefficient of dynamic friction should be 0.1 or more. The method for measuring the coefficient of dynamic friction is described later. do.
[0050] The air release time of the biaxially oriented polypropylene film of the present invention is preferably 10 seconds or less. More preferably, it is 8 seconds or less, even more preferably, it is 5 seconds or less, and particularly preferably The air release time is 3 seconds or less. If the air release time exceeds 10 seconds, the air may not be released when the material is rolled. The air release time is slow and wrinkles easily occur. The air release time should be 1 second or more. How to measure the air release time will be discussed later. The biaxially oriented polypropylene film of the present invention has a width of 300 mm and a roll length of 800 m or more. If the film is wound into a roll of the same size, it will be easy to transport, perform deposition processing, coating processing, and bag making. It is preferred for engineering. The biaxially oriented polypropylene film of the invention is wound up to a width of 500 mm and a length of 1000 m. When the wrinkles on the surface of the roll were visually evaluated according to the following criteria, there were slight wrinkles, but the wrinkles were not easily removed. It is preferable to apply a tension of about 20 N / m to the film so that the wrinkles disappear. It is more preferable.
[0051] When you want to improve the gas barrier properties and design of the biaxially oriented polypropylene film of the invention, Aluminum, polyvinylidene chloride, nylon, ethylene-vinyl alcohol copolymer, poly It is preferable to provide and use a layer, particularly a thin film layer, made of vinyl alcohol. The biaxially oriented polypropylene film of the present invention is partially coated with an aluminum thin film. It is preferable that the aluminum thin film layer is only partially peeled off. It is more preferable that there is no peeling of In addition, when a coating layer is provided on the surface of the biaxially oriented polypropylene film of the present invention, It is preferable that there is only a very small amount of cissing in the coating layer, and it is even more preferable that there is no cissing in the coating layer. preferable. The biaxially oriented polypropylene film of the present invention or a film having a thin film layer thereon, Low density polyethylene, linear low density polyethylene, ethylene-vinyl acetate copolymer, polypropylene Unstretched films, uniaxially stretched films, and biaxially stretched films made of propylene and polyester It is preferable to process the laminate into a packaging bag. Laminate of the biaxially oriented polypropylene film of the present invention and an unstretched polyethylene film The lamination strength is preferably 2.0N / 15mm or more, more preferably 2.3N / mm or more. It is preferable that the tension is 2.5 N / mm or more, more preferable that the tension is 2.5 N / mm or more, and particularly preferable that the tension is 2.8 N / mm or more. The laminate strength should be 5N / mm or less. The method for measuring the laminate strength will be described later.
[0052] (4) Manufacturing method The biaxially oriented polypropylene film of the present invention is a polypropylene film comprising a base layer (A). The polypropylene resin composition constituting the surface layer (B) and the polypropylene resin composition constituting the surface layer (C) The polypropylene resin compositions are melt-extruded by separate extruders and co-extruded from a die. The unstretched sheet is then cooled by a cooling roll to form an unstretched sheet, and the unstretched sheet is then stretched in the machine direction (MD ) and transverse direction (TD), and then heat-set. It is preferable that the surface layer (B) is extruded so as to come into contact with the cooling roll. When the opposite side comes into contact with the cooling roll, the polypropylene resin is gradually cooled and the degree of crystallinity increases. The arithmetic mean roughness (Ra) of the surface of the surface layer (B) becomes large due to the surface irregularities caused by spherulites. Sometimes it's too much. The melt extrusion temperature is preferably about 200 to 280°C. Within this temperature range, the layers can be easily extruded without being disturbed. In order to obtain a laminated film having a good appearance, the polypropylene resin composition constituting the base layer (A) is The viscosity difference (MFR difference) between the polypropylene resin composition constituting the surface layer (B) and the surface layer (C) is 6.0 It is preferable that the viscosity difference is 6 g / 10 min or less. The layer is easily disturbed, resulting in poor appearance. Most of the time it is 5.0g / 10min or less.
[0053] The surface temperature of the cooling roll is preferably 25°C or more and 35°C or less, and more preferably 27°C or more and 33°C or less. If the cooling roll temperature exceeds 35° C., the crystallinity of the polypropylene resin is The arithmetic mean roughness (Ra) of the surface of the surface layer (B) becomes large due to the surface irregularities of the formed spherulites. Sometimes it can become too much.
[0054] The lower limit of the stretching ratio in the machine direction (MD) is preferably 3 times, more preferably 3.5 times. If the thickness is less than the above range, the film thickness may become uneven. The maximum stretching time is 8 times, and more preferably 7 times. If the maximum stretching time exceeds the maximum stretching time, the subsequent TD stretching may become difficult. The lower limit of the MD stretching temperature is preferably 120° C., and more preferably The preferred temperature is 125° C., and more preferably 130° C. If the temperature is lower than the above range, the mechanical load becomes large. The thickness may become larger, the thickness may become uneven, or the film surface may become rough. The upper limit of the stretching temperature of D is preferably 160° C., more preferably 155° C., and The preferred temperature is 150°C. A higher temperature is preferred for reducing the thermal shrinkage rate, but This may cause adhesion, making it impossible to stretch the film, or cause the surface to become rough.
[0055] The lower limit of the stretching ratio in the transverse direction (TD) is preferably 4 times, more preferably 5 times. If the stretching time is less than the above range, the thickness may become uneven. The upper limit of the magnification is preferably 20 times, more preferably 17 times, and even more preferably It is preferably 15 times, and more preferably 12 times. If it exceeds the above range, the heat shrinkage rate becomes high, The film may break during stretching. The preheating temperature for TD stretching is set to the stretching temperature as soon as possible. In order to raise the temperature, it is preferably set to 5 to 15°C higher than the stretching temperature. The lower limit is preferably 150° C., more preferably 155° C., and even more preferably 1 If the temperature is lower than the above range, the material may not be sufficiently softened and may break. The upper limit of the TD stretching temperature is preferably 170°C. More preferably, the temperature is 168°C, and further preferably, 165°C. For this purpose, a higher temperature is preferable, but if the temperature exceeds the upper limit, the low molecular weight components melt and recrystallize, causing orientation. Not only will this reduce the strength of the film, but it may also cause the surface to become rough or the film to become white.
[0056] The stretched film is heat-set. The lower limit of the heat-setting temperature is preferably 163°C. If the temperature is less than the above range, the heat shrinkage rate may become high. In order to reduce the thermal shrinkage rate, a long treatment time is required, which may result in poor productivity. The upper limit of the temperature is preferably 176°C, more preferably 175°C. The low molecular weight components may melt and recrystallize, causing the surface to become rough and the film to turn white.
[0057] It is preferable to relax the film during heat fixation. The lower limit of the relaxation rate is preferably The thickness is preferably 2%, and more preferably 3%. If the thickness is less than the above range, the thermal shrinkage rate becomes high. The upper limit of the relaxation rate is preferably 10%, and more preferably 8%. If the thickness exceeds this value, the thickness may become uneven.
[0058] Furthermore, in order to reduce the thermal shrinkage rate, the film produced by the above process is once rolled. After winding into a roll, the film can be annealed offline.
[0059] The biaxially oriented polypropylene film thus obtained may be subjected to corona discharge, After plasma treatment, flame treatment, etc., the twin-axis arrangement of the present invention is wound up with a winder. A roll of polypropylene film can be obtained. EXAMPLES
[0060] The present invention will be described in more detail below with reference to examples, but the following examples are not intended to limit the present invention. However, any modifications that do not depart from the spirit of the present invention are included in the present invention.
[0061] (Measurement method) The raw materials used in the examples and comparative examples and the methods for measuring the physical properties of the obtained films are as follows: be.
[0062] 1) Mesopentad fraction ([mmmm] unit: %) The mesopentad fraction is measured by 13 The mesopentad fraction was determined using C-NMR. "Zambelli et al., Macromolecules, Vol. 6, p. 925 (1973) ) was calculated according to the method described in 13 C-NMR measurements were performed using a BRUKER AVA Using the "NCE500", 200 mg of sample was mixed with o-dichlorobenzene and heavy benzene in a ratio of 8:2 ( The mixture was dissolved at 135°C and heated to 110°C.
[0063] 2) Melt flow rate ([MFR]g / 10 min) The measurements were performed in accordance with JIS K7210 at a temperature of 230°C and a load of 2.16 kgf. In the case of raw resin, the pellets (powder) were weighed out and used in the required amount. In the case of film, the required amount was cut out and then cut into samples of approximately 5 mm square.
[0064] 3) Molecular weight and molecular weight distribution The molecular weight and molecular weight distribution of the raw resin and film were determined by gel permeation chromatography. The gel permeability was measured using gel permeation chromatography (GPC) with monodisperse polystyrene standards. The measurement conditions for the column, solvent, etc. are as follows. Solvent: 1,2,4-trichlorobenzene Column: TSKgel GMHHR-H(20)HT x 3 Flow rate: 1.0ml / min Detector: RI Measurement temperature: 140℃
[0065] The number average molecular weight (Mn), mass average molecular weight (Mw), and molecular weight distribution (Mw / Mn) are The molecular weights (M i ) molecule Number (N i ) is defined by the following formula: Number average molecular weight: Mn=Σ(N i M i ) / ΣN i Mass average molecular weight: Mw=Σ(N i M i 2 ) / Σ(N i M i ) Molecular weight distribution: Mw / Mn If the baseline is not clear, select the elution peak of the high molecular weight substance closest to the elution peak of the standard substance. The baseline is set to the lowest point of the high molecular weight side of the peak. did.
[0066] 4) Melting peak temperature (℃), melting peak area (J / g) Using a differential scanning calorimeter (DSC) manufactured by SII, the sample weight was 10 mg and the heating rate was 20°C / The melting endothermic peak temperature and the melting peak area were determined from the DSC curve.
[0067] 5) Thickness (μm) The thickness of each layer of the base material layer (A) and the surface layer (B) is a biaxially oriented laminated polypropylene film. The cross section of the modified urethane resin was cut out with a microtome and observed under a differential interference microscope. and measured.
[0068] 6) Haze (%) Measured at 23°C according to JIS K 7105. Haze meter (Nippon Denshoku Industries Co., Ltd.) The measurements were performed twice and the average value was calculated.
[0069] 7) Tensile modulus (GPa) Measured according to JIS K 7127. 10m wide in the longitudinal and transverse directions of the film. A sample measuring 180 mm in diameter and 180 mm in length was cut out using a razor. After leaving it in this atmosphere for 12 hours, measurements were taken at 23°C and 65% RH between the chucks. The measurement was performed at a distance of 100 mm and a pulling speed of 200 mm / min. The average of five measurements was taken. The measurement device used was an Autograph AG5000A manufactured by Shimadzu Corporation.
[0070] 8) Heat shrinkage rate (%) The measurements were made in accordance with JIS Z1712 using the following method. In each direction, the specimen was cut to a width of 20 mm and a length of 200 mm, and then subjected to hot air blowing at 150°C. The length was measured before and after heating, and the difference between the length before and after heating was The ratio (%) of the length minus the thickness to the length before heating was calculated to obtain the thermal shrinkage rate.
[0071] 9) Wetting tension (mN / m) In accordance with K 6768:1999, the film was aged at 23°C and 50% relative humidity for 24 hours. After aging, the corona-treated surface of the film was measured according to the following procedure. Step 1) The measurements were performed in a standard laboratory atmosphere (see JIS K 7100) with a temperature of 23°C and a relative humidity of 50%. This is done under the following conditions. Step 2) Place the test piece on the substrate of the hand coater (4.1) and apply a few drops of the test mixture onto the test piece. Drop the liquid and immediately pull the wire bar to spread it out. If a cotton swab or brush is used to spread the test mixture, the liquid should be spread to at least 6 cm 2 Below The amount of liquid should be enough to form a thin layer without pooling. do. The wetting tension is judged by observing the liquid film of the test mixture in a bright place and observing the state of the liquid film after 3 seconds. The liquid film is not broken and the condition when applied is maintained for more than 3 seconds. If the wetting continues for more than 3 seconds, the mixture is then transferred to the next highest surface tension liquid. Conversely, if the liquid film breaks within 3 seconds, proceed to the next mixture with a lower surface tension. Repeat this procedure to select the mixture that can accurately wet the surface of the test piece in 3 seconds. Oink. Step 3) Use a new swab for each test. The brush or wire bar should be cleaned until any residual liquid has evaporated. Since the composition and surface tension change depending on the evolution, it should be washed with methanol and dried after each use. Can. Step 4) Select the mixture that can wet the surface of the test piece in 3 seconds at least three times. The surface tension of the mixture thus selected is reported as the wetting tension of the film.
[0072] 10) Surface resistance value (LogΩ) In accordance with JIS K6911, the film was aged at 23°C for 24 hours, and then the film The surface layer (B) was measured.
[0073] 11) Coefficient of kinetic friction In accordance with JIS K7125, the surface layers (B) of two films are placed together, Measurements were taken at 23°C.
[0074] 12) Air release time (seconds) As shown in FIG. 1, a biaxially oriented polypropylene film is placed on a base plate 1 as a film 4. Then, the film holder 2 is placed on the film 4 so that the surface layer (B) faces upward. The film 4 is fixed in place while applying tension by placing it on top and fixing it in place. On the film holder 2, a biaxially oriented polypropylene film is placed as a surface layer ( C) is placed on the bottom. Next, film holder 8 is placed on top of film 5, and then The film holders 8, 2 and the base plate 1 are fixed together using screws 3. Next, the cavity 2a and the vacuum pump 6 provided in the film holder 2 are The vacuum pump 6 is then driven to connect the two parts through the hole 2c and the pipe 7. The film 5 is subjected to tension by being sucked into the cavity 2a. The overlapping surface of the film 4 and the film 5 is also filled with the film presser 2 through the circumferentially provided small holes 2. The pressure is reduced through d, and the film 4 and the film 5 are compressed from the outer periphery at their overlapping surfaces. They start to get closer together. The adhesion can be easily seen by observing the interference fringes from above the overlapping surfaces. Then, after interference fringes appear on the outer periphery of the overlapping surface of the film 4 and the film 5, The interference fringes spread across the front of the overlapping surfaces, and the time (in seconds) until the movement stops is measured. This time (seconds) is the air release time. The measurement was repeated five times by replacing the two films. Repeat this process several times and use the average value. In other words, the shorter the time (seconds), the better the film winding characteristics. It will be good.
[0075] 13) Martens hardness HMs (N / mm 2 ) The obtained film was cut into a square of about 2 cm, and the measurement surface was placed on a glass plate with a thickness of about 1 mm. After fixing the other side with adhesive, leave it in an atmosphere of 23℃ and 50% RH for 12 hours to condition the humidity. The specimen was subjected to a dynamic ultra-microhardness test using a Shimadzu Corporation DUH-211 " under the following measurement conditions using a method conforming to ISO14577-1 (2002). The measurement was carried out 10 times by changing the position of the film, and the average value of the 8 points excluding the maximum and minimum values was calculated. asked for.
[0076] <Measurement conditions> (setting) Measurement environment: Temperature 23°C, relative humidity 50% Test mode: Load-unload test Indenter used: Triangular pyramid indenter (made of diamond) with 115 degree inter-edge angle Indentation modulus: 1.140×106N / mm 2 Indenter Poisson's ratio: 0.07 Cf-Ap,As correction: Yes (conditions) Test force: 0.10mN ·Load speed: 0.0050mN / sec ·Load holding time: 5sec ·Unloading holding time: 0sec Martens hardness is measured at 50%F and 90%F (F = From the slope (m) of the relationship between the square root of the test force and the depth (0.10 mN), I asked. Martens hardness HMs=1 / (26.43×m 2 ) · · · · (1)
[0077] 14) Center surface average roughness ([SRa]μm) The center surface average roughness (SRa) of the obtained film was measured using a three-dimensional roughness meter (manufactured by Kosaka Laboratory, type ET-30HK) was used, the stylus pressure was 20mg, the measurement length in the X direction was 1mm, and the feed speed was 100μm / sec, Y-direction feed pitch 2μm, 99 recorded lines, height direction magnification 200 100x, cutoff 80μm, and calculated according to JIS-B0601(1994). The calculation was made according to the definition of surgical average roughness. The arithmetic mean roughness (SRa) was evaluated by averaging three trials each.
[0078] 15) Arithmetic mean roughness ([Ra] nm), maximum peak height ([Rp] nm), maximum valley depth ([R v]nm) The arithmetic mean roughness (Ra), maximum peak height (Rp), and maximum valley depth (Rv) of the obtained film The measurements were performed using a scanning probe microscope (Shimadzu Corporation, SPM-9700). The image was taken in dynamic mode with the measurement length in both the X and Y directions in a range of 2 μm. After correcting (tilt, line fit, noise line removal), ) was used to determine the arithmetic mean roughness.
[0079] 16) Laminate strength (N / 15mm) The laminate strength was measured by the following procedure. Step 1) Laminate of biaxially oriented polypropylene film and non-oriented polyethylene film Creating The lamination was carried out using a continuous dry laminating machine as follows. Adhesion to the surface layer (B) of the biaxially oriented polypropylene film obtained in the examples and comparative examples The amount of agent applied when dry is 2.8g / m 2 After gravure coating, the film is introduced into the drying zone. The sealant film was then dried at 80°C for 5 seconds. (Roll pressure: 0.2 MPa, roll temperature: 50°C). The obtained laminate The film was then aged at 40° C. for 3 days in a rolled state. The adhesive used was 28.9% by mass of base agent (TM569, manufactured by Toyo Morton Co., Ltd.) and 28.9% by mass of hardener (Toyo Morton CAT10L (4.00% by mass) and ethyl acetate (67.1% by mass) were mixed. The urethane adhesive obtained by this method was used, and the sealant film was made of non-oriented polyester manufactured by Toyobo Co., Ltd. A polyethylene film (Rix (registered trademark) L4102, thickness 40 μm) was used. Step 2) Measuring laminate strength The laminate film obtained above was stretched in the machine direction of the biaxially oriented polypropylene film. The specimen was cut into rectangular pieces (200 mm long, 15 mm wide) and subjected to a tensile test using a Tensilon. (manufactured by Orientec Co., Ltd.) was used to perform T-peel at a tensile speed of 200 mm / min in an environment of 23°C. The peel strength (N / 15mm) was measured when the laminate was peeled off. The measurement was carried out three times, and the average value was used. The strength was determined.
[0080] 17) Film roll wrinkle evaluation The biaxially oriented polypropylene film produced is wound up to a width of 500 mm and a length of 1000 m. The surface of the roll was visually evaluated for wrinkles according to the following criteria. ○: No wrinkles △: There are slight wrinkles, but the wrinkles disappear when a tension of about 20 N / m is applied to the pulled-out film. R ×: There are strong wrinkles, and the wrinkles do not disappear even when a tension of about 20 N / m is applied to the pulled-out film. stomach
[0081] 18) Court suitability evaluation Butanediol-vinyl alcohol copolymer (Nichigo-G, manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) -Polymer OKS-8049) was dissolved in a 15% aqueous solution of isopropyl alcohol and solidified. A coating solution with a molecular concentration of 5% was prepared. The prepared coating solution was dropped onto the surface layer (B) of the film. Then, dry with Mayer bar #3 at 0.2 g / m 2 The coating amount was adjusted to 100%. After that, the solution was thoroughly evaporated using a dryer, and the coating layer was visually evaluated for repelling. , ○ was considered a pass. ◎: No repelling of the coating layer 〇: 90% of the coating layer is free of repelling, but there is a small amount of repelling. △: There is some repellency in the coating layer, and the percentage of coating layers without repellency is less than 90%. ×: Cracks in the coating layer are present on the entire surface
[0082] 19) Aluminum deposition film adhesion evaluation A small vacuum deposition device (VWR, manufactured by ULVAC KIKOU CO., LTD.) was placed on the surface layer (B) of the film. The aluminum film thickness was 30 nm using a 300 / ERH vacuum vacuum chamber. The deposition surface of the deposited film was then coated with 18 mm of Nichiban Cellophane Tape (registered trademark). The adhesion of the aluminum vapor deposition film was evaluated using the 90° peeling method. A rating of ◯ was deemed to be acceptable. ○: No peeling of the aluminum vapor deposition film △: The aluminum vapor deposition film is partially peeled off. ×: Aluminum deposition film peeled off over the entire surface.
[0083] (raw resin) Details of the polypropylene resin raw materials used in the following examples and comparative examples and film formation conditions are as follows: Shown in Tables 1 to 3.
[0084] [Table 1]
[0085] [Table 2]
[0086] [Table 3]
[0087] Example 1 For the base layer (A), a polypropylene homopolymer PP-1 shown in Table 1 was used. The surface layer (B) is made of 43.2 layers of polypropylene homopolymer PP-1 shown in Table 1. 52.0% by weight of ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, The master batch A shown in Table 1 was used at a ratio of 4.8% by weight. Melt flow rate (g / 10 min) of polypropylene resin composition constituting surface layer (B) was 5.1. The surface layer (C) contains 93.6% by weight of the polypropylene homopolymer PP-1 shown in Table 1. Masterbatch A shown in Table 2 was used in a blend ratio of 6.4% by weight. The base layer (A) is extruded with a 45 mm extruder, the surface layer (B) is extruded with a 25 mm extruder, and the surface layer (C) is extruded with a 20 Using a 2.5 mm extruder, the raw resins were melted at 250°C and co-extruded into a sheet from a T-die. The surface layer (B) is cooled and solidified by contacting it with a cooling roll at 30°C. The film was stretched 4.5 times in the machine direction (MD). Then, in the tenter, the film was stretched in both transverse directions (TD). The ends are clipped, preheated at 168℃, and then stretched 8.2 times in the transverse direction (TD) at 155℃. The film was then heat-set at 165° C. while being relaxed by 6.7% in the transverse direction (TD). The above condition was designated as film formation condition a. Thus, a biaxially oriented polypropylene having a structure of surface layer (B) / base layer (A) / surface layer (C) was obtained. A polyester-based film was obtained. The surface of the surface layer (B) of the biaxially oriented polypropylene film is treated with SOFTAL-Corona-An Using a corona treatment machine manufactured by Do Plasma GmbH, the applied current was 0.75A. After corona treatment, the film was wound up on a winder. The thickness of the film was 20 μm ( The thickness of the surface layer (B) / base layer (A) / surface layer (C) is 1.3 μm / 17.7 μm / 1.0 The thickness was 1 μm.
[0088] Example 2 The thickness of the base layer (A) was pressed to 15.1 μm, and the thickness of the surface layer (B) was pressed to 3.9 μm. The same conditions as in Example 1 were used except for adjusting the amount of resin discharged from the extrusion machine. A polypropylene film was obtained.
[0089] Example 3 The surface layer (B) contains 45.0% by weight of the polypropylene homopolymer PP-1 shown in Table 1. The ethylene copolymerized polypropylene polymer PP-3 shown in Table 1 was used in an amount of 52.0% by weight, and the ethylene copolymerized polypropylene polymer PP-3 shown in Table 2 was used in an amount of 52.0% by weight. The same as Example 1 except that Masterbatch A was used at a ratio of 3.0% by weight. A biaxially oriented polypropylene film of 20 μm was obtained under the conditions.
[0090] Example 4 The surface layer (B) contains 1.2% by weight of the polypropylene homopolymer PP-1 shown in Table 1, The ethylene copolymerized polypropylene polymer PP-3 shown in Table 1 was used in an amount of 94.0% by weight, and the ethylene copolymerized polypropylene polymer PP-3 shown in Table 2 was used in an amount of 94.0% by weight. The same conditions as in Example 1 were used except that Starbatch A was mixed at a ratio of 4.8% by weight. As a result, a biaxially oriented polypropylene film of 20 μm was obtained.
[0091] Example 5 The polypropylene homopolymer PP-1 used in the base layer (A) and surface layer (C) is shown in Table 1. The same conditions as in Example 1 were used except that the film forming conditions were changed to b shown in Table 3. As a result, a biaxially oriented polypropylene film of 20 μm was obtained.
[0092] Comparative Example 1 The surface layer (A) contains 60.0% by weight of the polypropylene homopolymer PP-1 shown in Table 1. The surface layer (B) is a polypropylene homopolymer shown in Table 1. The mixture was 96.4% by weight of PP-1 and 3.6% by weight of Masterbatch A shown in Table 2. Other than that, the same conditions as in Example 1 were used to prepare a 20 μm biaxially oriented polypropylene film. Got it.
[0093] Comparative Example 2 The same conditions as in Example 1 were used except that the surface layer (B) was not subjected to corona treatment. A biaxially oriented polypropylene-based film was obtained.
[0094] Comparative Example 3 The surface layer (B) contains 45.0% by weight of the polypropylene homopolymer PP-1 shown in Table 1. The ethylene copolymerized polypropylene polymer PP-3 shown in Table 1 was used in an amount of 52.0% by weight, and the ethylene copolymerized polypropylene polymer PP-3 shown in Table 2 was used in an amount of 52.0% by weight. The master batch A was mixed at a ratio of 3.0% by weight, and the surface layer (C) was The same conditions as in Example 1 were used except that only the polypropylene homopolymer PP-1 shown in 1 was used. As a result, a biaxially oriented polypropylene film of 20 μm was obtained.
[0095] Comparative Example 4 The surface layer (B) contains 47.25% by weight of the polypropylene homopolymer PP-1 shown in Table 1. 52.00% by weight of ethylene copolymerized polypropylene polymer PP-3 shown in Table 1, The master batch B shown in the figure was mixed at a ratio of 0.75% by weight, and the surface layer (C) was The polypropylene homopolymer PP-1 shown in Table 1 was used in an amount of 98.4% by weight, and the masterbatch shown in Table 2 was used in an amount of 98.4% by weight. - Batch B was mixed at a ratio of 1.60% by weight, and the surface layer (C) was applied to the cooling roll. The film was formed under the same conditions as in Example 1, except that the film was formed so that the two layers were in contact with each other. A pyrene-based film was obtained.
[0096] Comparative Example 5 The base layer (A) contains 99.0% by weight of the polypropylene homopolymer PP-1 shown in Table 1. As an antistatic agent, stearyl diethanolamine stearate (KYM, Matsumoto Oil Co., Ltd.) The same conditions as in Example 1 were used, except that 1.0 wt% of 1.0-4K was used. A biaxially oriented polypropylene film of 1 μm was obtained.
[0097] Comparative Example 6 The film forming conditions were the same as in Example 1 except that the film forming conditions were changed to c in Table 3. An axially oriented polypropylene film was obtained.
[0098] The raw materials, production methods, and physical properties of the films used in the above Examples and Comparative Examples are shown in Tables 4 and 5.
[0099] [Table 4]
[0100] [Table 5]
[0101] The biaxially oriented polypropylene films obtained in Examples 1 to 5 have high lamination strength. There was no peeling of the aluminum deposition, and no repelling of the coating liquid, so the adhesion was excellent. In addition, the roll was free of wrinkles and had excellent blocking resistance. In contrast, the films of Comparative Examples 1 to 6 were all inferior in adhesion and roll winding condition. It was something like that. [Industrial Applicability]
[0102] The biaxially oriented polypropylene film of the present invention can be formed by deposition, coating, and bonding with other films. It exhibits excellent adhesion in lamination, and also has good slip properties and blocking resistance. It is suitable for industrial rolls. It can also be used for food packaging and labels for confectionery. In addition, the film can be produced at low cost, making it industrially useful.
Claims
1. The laminated ... The polypropylene-based resin composition constituting the surface layer (B) contains a polypropylene homopolymer and a polypropylene resin copolymerized with ethylene and / or an α-olefin having 4 or more carbon atoms in a ratio of 1% by weight / 99% by weight to 49% by weight / 51% by weight, the polypropylene resin composition constituting the surface layer (C) contains 0.5 mol % or less of units derived from ethylene and α-olefins having 4 or more carbon atoms; A biaxially oriented polypropylene film, wherein the surface layer (B) satisfies the following (1) to (5), (8), and (10), and the surface layer (C) satisfies the following (6), (7), and (9). (1) The wetting tension is 38 mN or more. (2) The surface resistance is 14.0 Log Ω or more. (3) The arithmetic mean roughness (Ra) is 3.0 nm or more and 5.5 nm or less. (4) Martens hardness of 248 N / mm 2 The following is the result. (5) The center surface average roughness (SRa) is 0.010 μm or more and 0.026 μm or less. (6) The center surface average roughness (SRa) is 0.020 μm or more. (7) Martens hardness of 270 N / mm 2 That's all. (8) The surface layer (B) is subjected to a corona treatment. (9) The surface layer (C) contains an antiblocking agent. (10) The surface layer (B) contains an antiblocking agent.
2. The biaxially oriented polypropylene film according to claim 1, wherein the surface layers (B) of the biaxially oriented polypropylene film have a dynamic friction coefficient of 0.6 or less at 23°C.
3. 3. The biaxially oriented polypropylene film according to claim 1, wherein the haze value of the biaxially oriented polypropylene film is 5% or less.
4. The biaxially oriented polypropylene film according to any one of claims 1 to 3, wherein the surface layer (B) has a maximum peak height Rp + maximum valley depth Rv of 30 nm or more and 50 nm or less.
5. The biaxially oriented polypropylene film according to any one of claims 1 to 4, wherein the air release time of the biaxially oriented polypropylene film is 10 seconds or less.
6. The biaxially oriented polypropylene film according to any one of claims 1 to 5, wherein the thickness of the biaxially oriented polypropylene film is 9 μm or more and 200 μm or less.
7. The polypropylene homopolymer contained in the polypropylene resin composition constituting the surface layer (B) has a lower melt flow rate than the copolymerized polypropylene resin.
8. A laminate of the biaxially oriented polypropylene film according to any one of claims 1 to 7 and a non-oriented polyethylene film.
9. The laminate according to claim 8, wherein the biaxially oriented polypropylene film and the unoriented polyethylene film have a laminate strength of 2.0 N / 15 mm or more.
Citation Information
Patent Citations
Biaxially stretched laminated polypropylene film
WO2017169952A1
Biaxially oriented polypropylene film
WO2017170244A1
Biaxially oriented polypropylene-based film
WO2018142983A1
Biaxially oriented polypropylene film
WO2007094072A1